International secondary science grade 6 workbook - Fullick, Ann; Philippa Gardom Hulme; Catherine Jones (Karachi: Oxford university press, 2023)
International Secondary Science has been developed in accordance with the guidelines of Pakistan National Curriculum 2022 framework. The textbooks are divided into the areas of physics, biology, and chemistry. The course has been designed to challenge students, and contains expanded material along with a multitude of practice questions in order to enhance understanding. It presents an interesting approach in which concepts are modelled with applicable situations. International Secondary Science is a comprehensive series accompanied by workbooks. Key features of the series: Comprehensive match to Pakistan National Curriculum 2022 framework Rigorous challenge materials that build a strong foundation for future learning Extensive preparation for the exams to build confidence and support performance Lots of crossover materials for seamless transition to higher levels
Keywords: Science